Peran Kurikulum K13 Dalam Penguatan Keterampilan Teknologi di SMK: Implikasi Untuk Pengembangan Kurikulum Merdeka - Sucoko, Sucoko; Erlisa, Dyan; Ismawati, Ismawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research explores the challenges in implementing the 2013 Curriculum (K13) in schools, especially those related to limited technological facilities and lack of technical training for teachers. Although K13 is designed to increase interactivity and develop 21st century skills, these operational constraints hinder the effectiveness of classroom learning. Limited access to technological devices and teachers' lack of technical understanding means that the learning process often does not reach the expected targets. This research suggests more comprehensive support from related parties, both in providing technological infrastructure and ongoing training for teachers. With this increased support, it is hoped that K13 implementation can run more optimally, supporting the curriculum objectives of producing graduates who are critical, competent and ready to face challenges in the digital era.